Investment and Infrastructure Development Projects in Public–Private Partnerships in Ukraine - Lozynska, Tamara; Birchenko, Nataliia; Piskun, Alona; Dengub, Valentyna (Dr. Viktor Koval, 2024)
Introduction. Acquiring sustainable development of the public-private partnership process is an urgent task, given the need for post-war reconstruction in Ukraine. Nowadays, development is suspended, which is experiencing an investment gap due to the risks and uncertainty of war conditions and insufficient guarantees for investors, an imperfect legal framework, and unresolved institutional problems. Therefore, the task of identifying obstacles to the development of public-private partnerships and improving their mechanisms arises. Aim and tasks. The study aims to analyse investment and infrastructure development projects within the framework of public-private partnership in Ukraine, identify barriers to sustainable development, assess the prospects for external financing and the need for private investment, develop proposals to increase the level of guarantees for investors and improve the mechanism of public-private partnership. Results. The need to change the principles of evaluating public-private partnership projects is indicated to facilitate the formation of a new paradigm of cooperation between society, business, and institutional structures during the post-war reconstruction of Ukraine. Obstacles to developing public-private partnerships, exceptionally high risks for investors, significant uncertainty caused by the war, insufficient investment guarantees, and the way to acquire a dynamic public-private partnership financial model are indicated. It is proposed that projects aimed at redistributing risks between project participants be diversified and fragmented, which will facilitate the involvement of SMEs in the public-private partnership mechanism. New approaches are proposed to increase the level of guarantees to investors and measures to improve the public-private partnership mechanism, which will provide the prerequisites for sustainable development. Conclusions. The conducted analysis showed that the improved mechanism of public-private partnership would reduce the risks of external investment by 28% and increase the chance of returning insured loans in case of failure by 11.9%, which increases guarantees for external creditors. This indicates that the total share of private investment in public-private partnership projects should reach 67%, and external investment should provide 75% of the total volume of investments.